Lectotypification of the name Carex setosa (Cyperaceae) - Ghosh, Asok (Phytotaxa, 2021)
Carex setosa Boott is a highly variable Sino-Himalayan species. In the protologue, the species was described by Francis Boott with three distinct morphotypes. Morphotypes were further illustrated in three different tabs. J.D. Hooker collected all the morphotypes in Lachen, Sikkim in 1849. The Indian morphotypes are Carex setosa var. setosa. The name Carex setosa is lectotypified here.